Development of an advanced nano-satellite VELOX-I – a micro-thruster system - Gay, Dexter Kai Wei. (2013)
This report aims to research and improve on the Nanosatellite to achieve better attitude determination and control on the functioning satellite. This will improve the overall capabilities and the efficiency of the satellite in Plasma Pulse Thruster. The aim was to improve the efficiency of the overall system by 200%